Geologistic aspects of railway passenger transportation in Ukraine - Shabliy, Oleh; Borsuk, Yurii (Human Geography Journal, 2021)
The passenger economy of the Ukrainian railway in the context of long-distance and suburban services has been analyzed. The basis of long-distance research is the share of certain categories (night speed, regional, night express, high-speed express Intercity+ and Intercity). Particular attention is paid to the distance of night high-speed trains over 1000 km within Ukraine. Regional routes are distinguished by length and route in different economic regions. This contributes to the selection of cities in nearby regions between which there is no direct connection. To characterize high-speed trains of the Intercity+ category, speed indicators are used, which allows to determine the best routes by speed. The reasons for the slow movement of some express trains have also been identified. The material shows the difference between the categories Intercity+ and Intercity. Only one of the class of night passenger trains is briefly mentioned, which is considered to be the most picturesque from the tourist point of view. Suburban service after the resumption of passenger traffic in early summer 2020 is described in detail. The most important indicator of this analysis is the number of suburban train pairs that were destined for transportation. Stations in each region are presented in tabular format, from which the movement to the endpoints is carried out. During the writing of the article, the largest passenger-intensive points were investigated in terms of the number of suburban transport flights and their administrative-territorial subordination to certain units was identified. In addition, areas with relatively low traffic of suburban trains and the causes of this socio-economic phenomenon are given. The problem of elongated routes serving sparsely populated areas, especially in the regions of southern Ukraine, has been identified. On the example of the longest suburban service, a human-geographical approach to reducing the number of stops has been proposed.